Effect of Cell Carrier Loading on Phenol Degradation in Association with Production of Exopolymeric Substances and Biofilm Characteristics during Start up and Steady State in a Pulsed Plate Bioreactor - B R Veena (International Journal of Pollution: Prevention & Control, 2024)
Biodegradation of phenol in a continuous pulsed plate bioreactor (PPBR) using immobilized bacterial cells has been shown to be a highly efficient process. The present paper reports the studies on the effect physical characteristics of biofilm (biofilm thickness, attached dry biomass and biofilm dry density) and chemical characteristics in terms of exopolymers viz. protein, carbohydrate and humic substance produced by Pseudomonas desmolyticum (NCIM 2112) bacterial cells immobilized on granular activated carbon during phenol degradation. The start-up time reduced from 12 to 10 h and the degradation of phenol was above 99% with increase in cell carrier loading from 80 to 120g of granular activated carbon (GAC). The increase in percentage degradation could be due to higher inoculum size. Also the net phenol removal rate was increased that could be due to increase in number of immobilized cells. The production of exopolymers increased and biofilm thickness decreased with increase in cell carrier loading. Increase in exopolymers could be due to higher consumption of phenol by microbial cells leading to higher production of exopolymers and also could be due to shear caused by cell to cell collision thus reducing biofilm thickness, increasing biomass and biofilm density.
Keywords: Biofilm; cell carrier loading; exopolymeric substance; phenol; pulsed plate bioreactor